2016
DOI: 10.1111/lam.12557
|View full text |Cite
|
Sign up to set email alerts
|

Induction of trap formation in nematode-trapping fungi by bacteria-released ammonia

Abstract: A total of 11 bacterial strains were assayed for bacteria-induced trap formation in the nematode-trapping fungus Arthrobotrys oligospora YMF1·01883 with two-compartmented Petri dish. These strains were identified on the basis of their 16S rRNA gene sequences. Volatile organic compounds (VOCs) of eight isolates were extracted using solid-phase micro-extraction (SPME) and their structures were identified based on gas chromatography-mass spectrometry (GC-MS). At the same time, all isolates were used for quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Thus, it was suggested that the exudate might have a function in pathogenesis. Ammonia is a predominant bacterial volatile organic compound that has been shown to induce trap formation in the nematode-trapping fungus Arthrobotrys oligospora ( Su et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was suggested that the exudate might have a function in pathogenesis. Ammonia is a predominant bacterial volatile organic compound that has been shown to induce trap formation in the nematode-trapping fungus Arthrobotrys oligospora ( Su et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ammonia metabolites in volatile organic compounds secreted by bacteria can also induce A. oligospora to produce traps, and a variety of nematodes also produce traps by ammonia [ 53 ]. Ammonia is a urea metabolite and functions as a signaling molecule to accelerate the switch from a saprophytic to a predatory lifestyle in NTF [ 54 ]. Certain bacteria can mobilize NTF to reduce predation pressure by producing and releasing urea [ 55 ].…”
Section: Mechanisms Of Trap Formation In a Oligosporamentioning
confidence: 99%
“…The VOC components of the samples were analyzed by GC-MS (7890A-5975C GC-MS system, Agilent Technologies, Santa Clara, CA, USA). The VOCs were identified from a database comparison of the mass spectrum of the substance with data banks (NIST) [23].…”
Section: Gas Chromatography-mass Spectrometry Assaymentioning
confidence: 99%